Boosting Listening Skills in Non-English Major Freshmen: Challenges and Solutions at Dong Nai Technology University - Hong, Tuyen Le Thi; Nhi, Huynh Nhu Yen; Nhi, Ha Thi Yen (International Journal of Asian Education, 2024)
This research investigates the difficulties non-major students face in English listening comprehension, focusing on those who have undergone a TOEIC-oriented English module. Listening is a critical skill for effective communication, yet many learners find it challenging. The study identifies specific listening obstacles and evaluates students' performance across different listening tasks. A descriptive statistical approach was employed, with data collected via a listening test based on the TOEIC format, administered to 190 first-year students at Dong Nai Technology University. Results indicate that students perform better in tasks involving discrete statements and responses but struggle significantly with conversations and monologues, which require more complex listening skills. The analysis reveals that while students can manage straightforward, detailed information, their inferencing abilities and handling of long, complex sentences are inadequate. These findings suggest a need for targeted instructional strategies to enhance listening comprehension, particularly in making inferences and processing detailed auditory information. Improving these skills is essential for students' overall listening proficiency and success in TOEIC and real-world communication.